The Internalization of Tasawuf Akhlaki Values: A Study of Youth in Shalawat Recitation through Hadrah Art - Artika; Hotmatua Paralihan; Zulkarnain (Sufiya Journal of Islamic Studies, 2025)
This study aims to explore the practice of reciting shalawat through the art of hadrah performed by the youth community in Jatikesuma Village, Deli Serdang. Using a field study method, primary data were obtained through participatory observation, in-depth interviews, and documentation of the hadrah players and their mentors. The research findings indicate that the practice of reciting 'shalawat' through the art of 'hadrah' generates spiritual expressions manifested within the players' inner experiences in two primary forms. First, the emergence of mahabbah (divine love) for Allah and the Prophet Muhammad PBUH; second, the internalization of exemplary values and character obtained through the appreciation of lyrics, music, and rhythms that provide a sense of khusyuk (deep devotion). These two forms of values have implications for strengthening the values of Akhlaki Sufism which significantly shape the personality of the youth to become more religious and well-mannered. Thus, hadrah art is effective as a means of spiritual character education in converting Sufistic values into ethical behavior at the grassroots level which is essential to maintain.